Beyond the GIST: A Case of Gastric Inflammatory Myofibroblastic Tumor - Hasan, Rakibul; Islam, Raisul; Lina, Mahbuba Akter (KYAMC Journal, 2026)
Primary inflammatory myo-fibroblastic tumor (IMT) is a very rare tumor. IMT in stomach is so rare that often misdiagnosed as gastric Gastro-Intestinal stromal Tumour (GIST). The prevalence, etiology and pathogenesis of this condition are still uncertain. It usually affects the lung and most commonly found in children and young patients. Despite the use of modern laboratory techniques and imaging, it is often difficult to make the diagnosis of IMT. So, diagnosis of gastric IMT is usually done post‑operatively by immunohistochemistry examination. Usually IMT is positive to SMA and vimentin. Complete surgical excision is the treatment of choice. Though recurrence is common. We report a rare case of gastric IMT in a 58-year-old male patient which was diagnosed as gastric GIST initially.